Estimation of herbaceous vegetation aerial cover estimation using remote sensing - Paz Pellat, Fernando (REVISTA TERRA LATINOAMERICANA, 2018)
To estimate biophysical variables, particularly foliage cover (fv), remote sensors can be used in different fields of application and facilitate model parameterization. From the perspective of radiation transfer models, the development of vegetation indexes (VI) should be based on theoretical considerations and experimental evidence, and there should be a linear relationship with the biophysical variable of interest. In this paper the theoretical considerations for the VI design are reviewed with a standardization format of the sol-sensor geometry and the use of normalized reflectances to consider the scale effect. From the use of radiation simulations, the Vegetation Index of Standardized Proportions in relation to the Limit Associated to Normalized spaces and their Attractors (VI_SPLANA) is introduced to establish a linear relationship with fv. The developed index is validated through multiple experiments on herbaceous vegetation, establishing its robustness and stability to be used in operational terms.